Implementation Gaps of the National Learning Recovery Program (NLRP) In the Schools Division of Sorsogon Province: An Analysis - Toca, Raul (JPAIR Institutional Research, 2026)
Persistent learning gaps in foundational literacy and numeracy have led education systems to implement learning recovery initiatives aimed at improving learner outcomes. In the Philippines, the Department of Education institutionalized the National Learning Recovery Program (NLRP) to address learning loss and strengthen instructional delivery. This study examined the implementation of the NLRP in the Schools Division of Sorsogon Province. Specifically, it aimed to identify implementation challenges, examine actions taken by school heads, explore opportunities in program implementation, and develop a localized implementation plan. An explanatory mixed-methods research design was employed. Quantitative data were collected using a researcher-developed survey questionnaire, while qualitative data were gathered through semi-structured interviews to further explain the quantitative results. Respondents consisted of public-school heads and teachers using total enumeration. Quantitative data were analyzed using descriptive statistics, whereas qualitative data were analyzed through thematic analysis. Findings indicated that NLRP implementation was influenced by systemic challenges related to instructional alignment, teacher preparedness, resource availability, administrative support, monitoring practices, learning environments, and stakeholder engagement. School heads addressed these challenges through adaptive leadership actions, including instructional guidance, coordination efforts, and stakeholder involvement, although effectiveness varied across school contexts. Opportunities emerged in strengthened teacher collaboration, improved instructional practices, and enhanced leadership engagement. The effective learning recovery requires context-responsive implementation and coordinated support mechanisms, highlighting the importance of a localized framework to enhance the effectiveness and sustainability of learning recovery initiatives.
Keywords: Implementation Gaps; National Learning Recovery; Action Taken; Opportunities; School Division